A New Aroma Index to Determine the Aroma Quality of Roasted and Ground Coffee During Storage - Krešimir Marin; Emil Zlatić; Andrej Plestenjak; Tomaž Požrl (Food Technology and Biotechnology, 2008)
The staling of ground roasted coffee blend was studied over one year of storage. Solid phase microextraction-gas chromatography-mass spectrometry analysis was carried out to identify and semi-quantify 40 volatile compounds. We focused on volatile compounds related to the ageing of coffee: methanethiol, propanal, 2-methylfuran, 2-butanone, 2,3-butanedione, 2-furfurylthiol and hexanal. Changes in sensory properties of coffee beverage prepared from the ground roasted coffee samples during storage in laminate packages (PET/ aluminium foil/PE) under air atmosphere, under nitrogen or in punctured packages were determined. Samples were stored at (23±2) °C and (40±10) % relative humidity. The reference coffee was packed similarly in laminate packages under nitrogen and stored at (-20±1) °C. Applying a statistical assessment of the results, we found the loss of most volatile compounds from all stored coffee samples, including even those stored under freezing conditions. The ratios of 2-methylfuran/2-butanone and methanethiol/hexanal proved useful indicators of staling. Our new proposed aroma index, the ratio of 2-furfurylthiol/ hexanal, proved to be the most effective, giving high correlation coefficients (R≥0.80) with aroma freshness for coffee brews prepared from the ground roasted coffee stored under different conditions at room temperature.